Characteristics of Wind Load on Spatial Structures with Typical Shapes due to Aerodynamic Geometrical Parameters and Terrain Type - Yi Zhou; Yuanqi Li; Yingying Zhang; Akihito Yoshida (Advances in Civil Engineering)
The characteristics of wind load on large-span roofs are complicated by their unique geometrical configurations and strong dependence on aerodynamic geometrical parameters and terrain type. However, there is rarely comprehensive research for characteristics of wind load on spatial structures due to aerodynamic geometrical parameters of roofs and terrain type. In this study, first, the effects of geometrical parameters of roofs and terrain type on the wind pressure distribution based on the data obtained from the existing wind tunnel tests were summarized. Then, the wind loads of full-scale structures were predicted by CFD, and the efficiency of numerical results was further verified by the available wind tunnel tests on spatial structures. Finally, with comparative analyses of the wind pressure distribution of the roofs predicted by CFD under different cases, the effects of shape ratios, especially rise-span ratio, height-span ratio, length-span ratio, and so on, and terrain type on the wind pressure field of typical spatial structures were presented. It can be beneficial to wind-resistant design of structures and can be provided as reference for aerodynamic design optimum of span spatial structures.